2008
DOI: 10.2106/jbjs.g.01095
|View full text |Cite
|
Sign up to set email alerts
|

Defining Substantial Clinical Benefit Following Lumbar Spine Arthrodesis

Abstract: We believe that thresholds of substantial clinical benefit for commonly used health-related quality-of-life measures following lumbar spine arthrodesis are important as they describe a magnitude of change that the patient recognizes as a major improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
234
4
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(246 citation statements)
references
References 18 publications
5
234
4
3
Order By: Relevance
“…Our data differ from other studies, since we not only measured the pain, but also determined the function and QOL. It is noteworthy that our study also shows that not only the differences in the VAS, ODI and SF-36 scores between the groups with curves \10°, 10°-19°and C20°d o not reach statistical significance, but also the median values of the three groups do not reach a minimal clinically important difference either [17,18]. This is important ,since a potential pitfall in evaluating pain, disability and QOL is considering only the statistical differences in outcome scores but not the clinical relevance of those differences.…”
Section: Discussioncontrasting
confidence: 61%
“…Our data differ from other studies, since we not only measured the pain, but also determined the function and QOL. It is noteworthy that our study also shows that not only the differences in the VAS, ODI and SF-36 scores between the groups with curves \10°, 10°-19°and C20°d o not reach statistical significance, but also the median values of the three groups do not reach a minimal clinically important difference either [17,18]. This is important ,since a potential pitfall in evaluating pain, disability and QOL is considering only the statistical differences in outcome scores but not the clinical relevance of those differences.…”
Section: Discussioncontrasting
confidence: 61%
“…A recent review proposed an MIC cutoff for the ODI of ten points, or 30% improvement from baseline [8]. Several studies have identified MIC cutoffs for the NRS back pain and leg pain from 2 to 2.5 [8,9]. In addition, cutoffs for substantial clinical improvements, such as ''success'' after lumbar disc surgery, have been reported both for the ODI (20), NRS back pain (2.5), NRS leg pain (3.5), and EQ-5D (0.3) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified MIC cutoffs for the NRS back pain and leg pain from 2 to 2.5 [8,9]. In addition, cutoffs for substantial clinical improvements, such as ''success'' after lumbar disc surgery, have been reported both for the ODI (20), NRS back pain (2.5), NRS leg pain (3.5), and EQ-5D (0.3) [9][10][11]. A large proportion of the patients are difficult to classify as either improved, unchanged, or worse after surgery [12].…”
Section: Introductionmentioning
confidence: 99%
“…It was originally described for patients who were surgically treated for lumbar degenerative disease and defined as clinical improvement that represented a substantial clinical benefit after treatment [3]. The method was similar to some of those used for constructing MCID [2].…”
Section: Introductionmentioning
confidence: 99%
“…The method was similar to some of those used for constructing MCID [2]. The patients rated their situation compared to the situation 1 year before [3].…”
Section: Introductionmentioning
confidence: 99%